Unveiling Halliday’s Textual Metafunction in Indonesian and Samoan EFL Textbooks for Year 10 - Aulia, Tazkia Aghnia; Fitriati, Sri Wuli; Widhiyanto (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Abstract. Textual metafunction helps the authors develop text coherently and cohesively and significantly aids readers in understanding the idea, especially in EFL textbooks. EFL textbook has become the essential learning material in EFL classrooms which it should be delivered with clarity to fostered students to grasp the material. Due to the crucial role of EFL textbooks in EFL classrooms, this study aims to unveil how theme-rheme and thematic progression occurred in reading passages of Indonesian and Samoan EFL textbooks. To attain the aims of the study, twelve reading passages from the Indonesian EFL textbook and eight reading passages from the Samoan EFL textbook for year ten were examined. Data that has been examined by theme-rheme proposed by Halliday and Matthiessen (2014) revealed that topical theme is a common type of theme found in Indonesian and Samoan EFL textbooks. Concurrently, these textbooks have the same type order in the occurrence of theme-rheme’s type, from the most common to the least type of theme that appeared. However, the Samoan EFL textbook contains a smaller variety of components in theme types due to the limited text genres in it. After examined thematic progression of these textbooks, and it revealed that the zigzag theme pattern was the majority theme pattern. Alongside the zigzag theme pattern becoming the majority pattern, these textbooks had different order for the second and third place of theme pattern due to the various contents of these EFL textbooks. This study provides textual metafunction, especially theme-rheme and thematic progression, which could be analyzed in EFL textbooks and, eventually, in literary texts.